Analisis Minat Masyarakat Dalam Memilih Bank Mekaar Dibandingkan Bank Syariah Sebagai Sumber Pembiayaan Usaha Mikro Studi Kasus di Desa Gerisak Semanggeleng, Kecamatan Sakra Barat - Nora Susilawati; Hikmatul Hidayati MZ; Fathurrazak Fathurrazak (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The purpose of this study is to identify the factors that influence public interest in choosing Bank Mekaar compared to Islamic Banks (Bank Syariah) as a source of micro-business financing. This research employs a qualitative method with a descriptive approach, where data were collected through in-depth interviews, direct observations, and documentation of micro-entrepreneurs in Gerisak Semanggeleng Village. Data analysis was carried out through three stages: data reduction, data display, and conclusion drawing. The findings reveal that people are more interested in Bank Mekaar because of its simple loan application process, absence of collateral requirements, and fast fund disbursement. The ease and efficiency of services are key factors for micro-entrepreneurs who need quick access to capital. In contrast, the low interest in Islamic banks is mainly due to the lack of socialization, limited public understanding of the profit-sharing system, and the perception that Islamic bank procedures are more complex and time-consuming. Financing from Bank Mekaar has proven beneficial in helping people increase their capital, expand their businesses, and improve household income. Therefore, it can be concluded that procedural simplicity, service speed, and limited outreach from Islamic banks are the main factors influencing people’s preference for Bank Mekaar as a source of micro-business financing.